Trends in cocaine use, markets and harms in Australia, 2003–2019. (24th February 2021) - Man, Nicola; Chrzanowska, Agata; Price, Olivia; Bruno, Raimondo; Dietze, Paul M.; Sisson, Scott A.; Degenhardt, Louisa; Salom, Caroline; Morris, Leith; Farrell, Michael; Peacock, Amy
Abstract: Introduction: This paper aims to describe cocaine use, markets and harms in Australia from 2003 to 2019. Methods: Outcome indicators comprised prevalence of use from triennial household surveys; patterns of use from annual surveys of sentinel samples who use stimulants; and cocaine‐related seizures, arrests, hospitalisations, deaths and treatment episodes. Bayesian autoregressive time‐series analyses were conducted to estimate trend over time: Model 1, no change; Model 2, constant rate of change; and Model 3, change over time differing in rate after one change point. Results: Past‐year population prevalence of use increased over time. The percentage reporting recent use in sentinel samples increased by 6.1% (95% credible interval [CrI95% ] 1.2%, 16.9%; Model 3) per year from around 2017 (48%) until the end of the series (2019: 67%). There was a constant annual increase in number of seizures (count ratio: 1.1, CrI95% 1.1, 1.2) and arrests (1.2, CrI95% 1.1, 1.2), and percentage reporting cocaine as easy to obtain in the sentinel samples (percent increase 1.2%, CrI95% 0.5%, 1.8%; Model 2). Cocaine‐related hospitalisation rate increased from 5.1 to 15.6 per 100 000 people from around 2011–2012 to 2017–2018: an annual increase of 1.3 per 100 000 people (CrI95% 0.8, 1.8; Model 3). While the death rate was low (0.23 cocaine‐related deaths per 100 000 people in 2018; Model 2), treatment episodes increased from 3.2 to 5.9 per 100 000 people from around 2016–2017 to 2017–2018: an annual increase of 2.9 per 100 000 people (CrI95% 1.6, 3.7; Model 3). Discussion and Conclusions: Cocaine use, availability and harm have increased, concentrated in recent years, and accompanied by increased treatment engagement.